Training on Designing UI/UX using Design Thinking and Figma at SMKN 4 Bandung - Umaroh, Sofia; Yudianto, Fauzi; Istifah, Istifah (Institut Teknologi Nasional, Bandung, 2024)
The emergence of User Interface (UI) and User Experience (UX) Design in the world is now attracting more people who want to learn about it. SMKN 4 Bandung is one of the schools that have an industry-class curriculum, where students are provided with a learning program related to industrial technology. This training is divided into three stages: Pre-Test, Training, and Post-Test. The Pre-Test is used to assess the extent of their understanding of UI and UX. During the training process, there is an introduction and implementation of UI and UX concepts. The results of the Pre-Test showed that 90% of the students were not familiar with UI and UX. The Post-Test results confirm that, overall, this community engagement in the industrial class on UI and UX has successfully improved the knowledge of the students of SMKN 4 Bandung, with a N-gain score of 0.45 considered medium improvement.